Application of PCR, rep-PCR and RAPD techniques for typing of Lactococcus lactis strains - Prodelalová, J; Spanová, A; Rittich, B (Folia microbiologica, 2005)
A collection of 34 lactococcal strains were characterized using the polymerase chain reaction (PCR) for the acmA gene, and for the 16S rDNA gene, and DNA fingerprinting methods for randomly amplified polymorphic DNA (RAPD) and repetitive extragenic palindrome-PCR (rep-PCR). PCR experiments corroborated the genotypic identification of Lactococcus lactis strains by RAPD; rep-PCR did not distinguish between L. lactis subspecies. In some cases, phenotypic classification of L. lactis subspecies did not correlate with genotypic characterization.
Keywords: ribozomální DNA; Phenotype; Repetitive Sequences, Nucleic Acid; DNA, Ribosomal; polymerázová řetězová reakce; Polymerase Chain Reaction; technika náhodné amplifikace polymorfní DNA; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; Muramidase; repetitivní sekvence nukleových kyselin; Random Amplified Polymorphic DNA Technique; muramidasa; Bacterial Typing Techniques; techniky typizace bakterií; fenotyp; RNA ribozomální 16S; Lactococcus lactis